Dermoscopy use in UK primary care: a survey of GPs with a special interest in dermatology. (17th May 2019) - Jones, O.T.; Jurascheck, L.C.; Utukuri, M.; Pannebakker, M.M.; Emery, J.; Walter, F.M.
Abstract: Background: Melanoma accounts for 90% of skin cancer mortality and typically presents in primary care, where it can be challenging to distinguish from benign lesions. Dermoscopy is a tool for skin visualization that is routinely used for melanoma diagnosis in secondary care. However, the role of dermoscopy in primary care remains unclear. Objectives: To determine views on, and use of, dermoscopy by dermatology‐interested general practitioners (GPs). Methods: An online questionnaire was emailed to the UK Primary Care Dermatology Society members in February 2018, and responses collected over the following 4 weeks. Results: A total of 205 responses were analysed. Most respondents were GPs (94%), aged over 50 (53%), had a postgraduate dermatological qualification (67%) and used dermoscopy regularly when reviewing pigmented skin lesions (97%). Dermoscopy use was commoner amongst GPs who had worked longer in primary care and had experience of secondary care dermatology. Most had undertaken training in dermoscopy (91%), although one‐fifth (20%) had not updated their training in over 5 years. Most of those who had received only 1 day of face‐to‐face training reported feeling confident using a dermatoscope. Few respondents (11%) reported access to teledermatology or teledermoscopy for urgent or routine referrals. Conclusions: UK GPs with a special interest in dermatology are routinely using dermoscopy in the primary care setting. More research is needed to establish optimal approaches to training and updating GP dermoscopy skills. When dermoscopy has been shown to be safe, effective, acceptable and cost‐effective in this setting, more GPs may also be able to gain and maintain the skills to implement dermoscopy into routine primary care. Technological advances, including incorporation of artificial intelligence (AI) and algorithms to guide GPs, could also contribute to widening use of dermoscopy among GPs.